Caecal dilatation and dislocation in 20 dairy cows. A retrospective study. - Proios, I; Hoedemaker, M; Kiossis, E (Journal of the Hellenic Veterinary Medical Society, 2024)
A total of 20 cows with caecal dilatation and dislocation were included in this retrospective study. The aim of the study was to describe the findings of the initial clinical examination, the haematological, biochemical and venous blood gas analysis as well as the therapeutic management and the surgical findings of these cases. A positive simultaneous percussion and auscultation in the right flank as well as rectal palpation of the distended caecum were the most common findings in 90% of the animals. Increased haematocrit, hyperlactateaemia and hyperglycaemia were the most often occurring laboratory findings. Conservative treatment using neostigmine s.c. (0.025mg/kg) was successful in three out of four cases. Surgical therapy including laparotomy in the right flank and typhlotomy was performed in 17 cases. Caecal dilatation (n=9), retroflexion (n=4) and torsion (n=4) were revealed intraoperatively. During surgery in three cows, the caecum had filled once again with fluid content and typhlotomyhad to be repeated. Typhlectomy was not necessary in any of these cows. A relaparotomy due to recurrence of the caecal disorder was not required in any of the cases during hospitalisation. The postsurgical treatment included antibiotics, neostigmine in all cows and fluid therapy in the majority of the animals. Laxative treatment using 250 g sodium sulphate twice daily per os was applied in 10 cases. All cows were discharged from the clinic and returned to the farm.